A critical review of nitrogen mineralization in biosolids-amended soil, the associated fertilizer value for crop production and potential for emissions to the environment. - Rigby, H.; Clarke, B.; Pritchard, Deborah; Meehan, B.; Beshah, F.; Smith, S.; Porter, N. (Elsevier BV, 2015)
International controls for biosolids application to agricultural land ensure the protection of human health and the environment, that it is performed in accordance with good agricultural practice and that nitrogen (N) inputs do not exceed crop requirements. Data from the scientific literature on the total, mineral and mineralizable N contents of biosolids applied to agricultural land under a wide range of climatic and experimental conditions were collated. The mean concentrations of total N (TN) in the dry solids (DS) of different biosolids types ranged from 1.5% (air-dried lime-treated (LT) biosolids) to 7.5% (liquid mesophilic anaerobic digestion (LMAD) biosolids). The overall mean values of mineralizable N, as a proportion of the organic N content, were 47% for aerobic digestion (AeD) biosolids, 40% for thermally dried (TD) biosolids, 34% for LT biosolids, 30% for mesophilic anaerobic digestion (MAD) biosolids, and 7% for composted (Com) biosolids. Biosolids air-dried or stored for extended periods had smaller total and mineralizable N values compared to mechanically dewatered types. For example, for biosolids treated by MAD, the mean TN (% DS) and mineralizable N (% organic N) contents of air-dried materials were 3% and 20%, respectively, compared to 5% and 30% with mechanical dewatering. Thus, mineralizable N declined with the extent of biological stabilization during sewage sludge treatment; nevertheless, overall plant available N (PAN=readily available inorganic N plus mineralizable N) was broadly consistent across several major biosolids categories within climatic regions. However, mineralizable N often varied significantly between climatic regions for similar biosolids types, influencing the overall PAN. This may be partly attributed to the increased rate, and also the greater extent of soil microbial mineralization of more stable, residual organic N fractions in biosolids applied to soil in warmer climatic zones, which also raised the overall PAN, compared to cooler temperate areas. It is also probably influenced by differences in upstream wastewater treatment processes that affect the balance of primary and secondary, biological sludges in the final combined sludge output from wastewater treatment, as well as the relative effectiveness of sludge stabilization treatments at specific sites. Better characterization of biosolids used in N release and mineralization investigations is therefore necessary to improve comparison of system conditions. Furthermore, the review suggested that some international fertilizer recommendations may underestimate mineralizable N in biosolids, and the N fertilizer value. Consequently, greater inputs of supplementary mineral fertilizer N may be supplied than are required for crop production, potentially increasing the risk of fertilizer N emissions to the environment. Thus greater economic and environmental savings in mineral N fertilizer application are potentially possible than are currently realized from biosolids recycling programmes.